Sociocultural projects “Sverdlovsk: Cultural evacuation” and “The Urals are speaking!”: Conception and implementation in the context of the formation of local patriotism - Elena A. Azanova; Zhaudet I. Iskhakov (Управление культурой)
In 2021-2022 in Ekaterinburg, two sociocultural projects were implemented - "Sverdlovsk: cultural evacuation" and "The Ural is speaking!". The initiators are the journalists of the portal of the Department of Culture, who conducted historical research, substantiated projects, selected a team, partners, controlled the content of cultural products and themselves became actors of the verbatim performance. The projects were implemented sequentially at the expense of the municipal budget, partner resources and received grants for a total of 2,649,086 rubles. Both projects are aimed at promoting the cultural heritage of Russia and the study of regional history and local identity. The purpose of the article is to present a management case for the preparation, implementation and measurement of project performance. The methods used in the framework of the projects are the historical method, questionnaires, and social media analysis were used. The projects represented one historical period and phenomenon (the evacuation of cultural institutions to Sverdlovsk during the Great Patriotic War and the impact on the city's cultural sphere), but used different presentation formats (a documentary performance within the walls of the Hermitage-Ural Cultural and Educational Center, lectures and master- classes with elements of theatricalization, multi-genre immersive concerts with the use of historical reconstruction). In the cases described, the most modern management approaches are used - reliance on analytics (collection of historical information, analysis of statistics and audience survey results), fundraising, partnerships between private and municipal / state cultural and educational institutions, participatory technologies, active media support. The key characteristics of the described projects are the emphasis on a new aspect of a well-known theme; the use of modern and demanded by the audience forms of embodiment (verbatim, concerts, processions, etc.); the complexity of presenting the topic through partnerships; appeal to different forms of culture and art (theater, music, museum); emphasis on narratives about famous people representing the situation; shaping the economy through a combination of municipal budget funds and grants. Consistently initiated and implemented in 2021-22 sociocultural projects "Sverdlovsk: cultural evacuation" and "The Urals are speaking!" have become an important form of promoting the cultural sphere of the city of Ekaterinburg, an effective tool for creating a community around the website of the Department of Culture of Ekaterinburg, a way to research and promote the topic of evacuation during the Great Patriotic War by involving citizens in projects to form local patriotism.